1970
DOI: 10.4267/pollution-atmospherique.4804
|View full text |Cite
|
Sign up to set email alerts
|

Distribution spatiale des O3, NOx et SO2 et évaluation des interactions troposphériques sur la ville de Tunis (Tunisie)

Abstract: Cette étude évalue la pollution urbaine en O 3 , NO x et SO 2 et les interactions locales avec les paramètres météorologiques de la capitale Tunis (Tunisie) entre 2003 et 2014. Elle permet d'établir des cartes de la distribution de la pollution gazeuse puis, par une approche statistique d'étude de la corrélation et d' Analyse en Composantes Principales (ACP), d'établir les interactions existant entre les paramètres météorologiques et les concentrations en ozone et oxydes d'azote. Des concentrations élevées en … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This is due in part to the disruptive factors affecting the environment, which are continually increasing as a result of changes in standard methods of analysis, as well as a lack of data (Rahman, 2017). Kchih et al (2015), for Tunisia, and Lana et al (2016), for Madrid, investigated the dynamics among urban air pollution, and meteorological conditions, modelling a high-resolution hourly data in a regression framework. The author found the temperature to be a less influential factor of air pollution for the given area and time.…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…This is due in part to the disruptive factors affecting the environment, which are continually increasing as a result of changes in standard methods of analysis, as well as a lack of data (Rahman, 2017). Kchih et al (2015), for Tunisia, and Lana et al (2016), for Madrid, investigated the dynamics among urban air pollution, and meteorological conditions, modelling a high-resolution hourly data in a regression framework. The author found the temperature to be a less influential factor of air pollution for the given area and time.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Kchih et al (2015), for Tunisia, and Lana et al (2016), for Madrid, investigated the dynamics among urban air pollution, and meteorological conditions, modelling a high-resolution hourly data in a regression framework. The author found the temperature to be a less influential factor of air pollution for the given area and time.…”
Section: Review Of Literaturementioning
confidence: 99%
“…This is in agreement with the present study which revealed the influence of the city of Cotonou, especially the major intersections, by PM 2.5 and TCOV. This trend is also reported by [4] who showed that the city of Kinshasa in the Democratic Congo is also polluted by NO 2 and CO. [17], while working in the city of Tunis in Tunisia noticed high concentrations of ozone in the study area, and their distribution opposite to that of concentrations of nitrogen oxides and sulfur dioxide, even if the values of the latter do not exceed the standards (respectively. The correlation matrix as well as the PCA made it possible to note a strong correlation between ozone, temperature and the intensity of solar radiation, on the one hand, and the relative humidity of the air and the concentration of nitrogen monoxide, on the other hand, these two groups being anti-correlated.…”
Section: Discussionmentioning
confidence: 70%